Making Use of Poems to Teach English - Tütüniş, Birsen; Çetinavcı, Uğur Recep (My University, 2012)
This study was motivated by the fact that there is a tendency to see poetry as being remote from language teaching contexts. Thinking that this is partly because of the lack of training in teaching literature given to English language teacher trainees, an experimental group of 3rd year Uludag University English Language Teaching (ELT) Department students taking the “Poetry Analysis and Teaching” course were taught about new poetry-centered techniques and activities compiled from the related literature and they were asked to design a lesson using them. The control group continued to take the course without any changes. At the end of the term, both groups were given a questionnaire on their attitudes towards the use of poetry in EFL and statistically significant differences were found between the groups showing that the experimental group favored poetry more strongly as a multi-purpose and multi-functional tool to teach a foreign language.
Keywords: poetry; language teaching; EFL; poetry analysis; teacher training; poems